Interploidy gene flow via a 'pentaploid bridge' and ploidy reduction in Cystopteris fragilis fern complex (Cystopteridaceae: Polypodiales) - Ptáček, Jan; Ekrt, Libor; Hornych, Ondřej; Urfus, Tomáš (Plant reproduction, 2023)
Our results indicate the existence of interploidy gene flow in Cystopteris fragilis, resulting in sexual triploid and diploid gametophytes from pentaploid parents. Similar evolutionary dynamics might operate in other fern complexes and need further investigation. Polyploidization and hybridization are a key evolutionary processes in ferns. Here, we outline an interploidy gene flow pathway operating in the polyploid Cystopteris fragilis complex. The conditions necessary for the existence of this pathway were tested. A total of 365 C. fragilis individuals were collected covering representatives of all three predominant ploidy levels (tetraploid, pentaploid, and hexaploid), cultivated, had their ploidy level estimated by flow cytometry, and their spores collected. The spores, as well as gametophytes and sporophytes established from them, were analysed by flow cytometry. Spore abortion rate was also estimated. In tetraploids, we observed the formation of unreduced (tetraploid) spores (ca 2%). Collected pentaploid individuals indicate ongoing hybridization between ploidy levels. Pentaploids formed up to 52% viable spores, ca 79% of them reduced, i.e. diploid and triploid. Reduced spores formed viable gametophytes, and, in the case of triploids, filial hexaploid sporophytes, showing evidence of sexual reproduction. Some tetraploid sporophytes reproduce apomictically (based on uniform ploidy of their metagenesis up to filial sporophytes). Triploid and diploid gametophytes from pentaploid parents are able to mate among themselves, or with "normal" reduced gametophytes from the sexual tetraploid sporophytes (the dominant ploidy level in the sporophytes in this populations), to produce tetraploid, pentaploid, and hexaploid sporophytes, allowing for geneflow from the pentaploids to both the tetraploid and hexaploid populations. Similar evolutionary dynamics might operate in other fern complexes and need further investigation.
Keywords: Sporogenesis; Ferns; Flow cytometry; Apomixis; Cystopteris; Ploidy reduction; Interploidy gene flow; Mixed mating; Gametophytes; Diplospores